PAX-5: A Valuable Immunohistochemical Marker in the Differential Diagnosis of Lymphoid Neoplasms - Desouki, Mohamed M. (Marshfield Clinic, 2010)
Objective: Undifferentiated tumors and hematolymphoid neoplasms can be diagnostically challenging due to potential overlap of morphologic features and variant antigen expression. PAX-5, a transcription factor expressed throughout B-cell maturation, is detected in most B-cell neoplasms including those that lack expression of mature B-cell markers, such as classical Hodgkin lymphoma (cHL), B-lymphoblastic leukemia and B-cell lymphomas following rituximab therapy. The lack of PAX-5 expression in most CD30-positive non-hematopoietic malignancies (embryonal carcinoma and seminoma) and T-cell lymphomas, such as anaplastic large cell lymphoma (ALCL), suggests that the absence of PAX-5 may be used to confirm non-B-cell lineage. The goal of this study was to retrospectively assess PAX-5 immunoreactivity in diagnostic samples of hematolymphoid and other non-hematopoietic malignancies. Design: Diagnostic lymph node, decalcified core bone marrow biopsies and tissue sections from 111 archived paraffin-embedded tissue blocks and a tissue lymphoma microarray were immunostained using a monoclonal antibody to PAX-5. The corresponding hematoxylin and eosin stained tissue sections and additional immunostains were simultaneously evaluated. PAX-5 immunoreactivity in neoplastic cells was scored as positive or negative. This study was exempted by the Institutional Review Board for Human Research. Results: Nuclear PAX-5 immunoreactivity was detected in 88% (36/41) of Hodgkin lymphoma, all cases of diffuse large B-cell lymphoma (n=72), small B-cell lymphomas (n=5), B-lymphoblastic leukemia/lymphoma and mixed phenotype acute leukemia with B-cell lineage (n=5). PAX-5 was not detected in ALCL (n=22), T-cell lymphoblastic leukemia/lymphoma, mixed phenotype acute leukemia with T-cell lineage (n=5), acute myeloid leukemia (n=4), carcinoid tumors with typical morphology (n=5), melanoma (n=3), and undifferentiated/metastatic tumors (n=8). Non-neoplastic bone marrow sections showed scattered nuclear staining in small B-cell lymphocytes/hematogones. The detection of PAX-5 immunoreactivity resulted in the reclassification of two cases of ALCL to cHL. Conclusion: Overall, our results demonstrate that including PAX-5 in a panel with other immunomarkers helps establish B-cell lineage and increases diagnostic yield.